THE CULTURAL MEANING IN THE PREGNANCY TRADITIONS IN KEBUMEN: ANTHROPOLINGUISTIC STUDY - Saadiah, Nur Khofifah (Acintya, 2025)
The Javanese are one of the ethnic groups with many traditions. In the tradition they practice, there is a specific meaning and purpose. One of them is the slametan tradition, which aims to pray to God for the smooth running of the event that will be held. A tradition that is still deeply ingrained and rich in language that can be studied is the pregnancy tradition, which includes several special rituals such as mitoni, mapati, and muputi. This research begins the discussion of tradition with primary data consisting of linguistic data collected in Kebumen, Central Java. This research uses an anthropological linguistics approach. Then, to obtain data, the researcher conducted interviews with a woman who had just completed a series of pregnancy traditions and an elderly woman who understood the cultural significance of pregnancy traditions. The research results show that there is a categorization in pregnancy traditions, namely: two prohibitions, eight beliefs, and five conditions. The overall categorization has a deep meaning in terms of language.